An Analysis of Corporate Social Responsibility Practices and Their Impact on Local Communities in the Case of Samsung Electronics in India - Arjun Rajesh Kumar; Isha Mehta (Studies in Social Science & Humanities, 2024)
This paper delves into Samsung Electronics’ corporate social responsibility (CSR) initiatives in India and assesses their impact on local communities. It examines a range of programs aimed at social and economic development, from educational enhancements to healthcare access and environmental sustainability. The study seeks to provide a nuanced understanding of how these initiatives are planned, executed, and received by the communities they intend to serve. The analysis includes an exploration of Samsung’s Smart Class Program, which has transformed educational experiences by integrating digital technologies into classrooms in underserved areas. This initiative’s effect on student engagement and learning outcomes is evaluated to gauge its contribution to educational advancement. The paper also investigates Samsung’s healthcare projects, such as the deployment of mobile healthcare units and telemedicine centers, which have been instrumental in bringing medical services to remote and marginalized communities. Additionally, the research addresses the challenges Samsung faces in implementing its CSR initiatives, including issues of scalability and sustainability. It discusses the strategies the company has employed to overcome these hurdles and the lessons learned from these experiences. The paper emphasizes the importance of collaboration between corporations, government entities, and NGOs in enhancing the effectiveness of CSR activities. The paper provides a comprehensive overview of Samsung Electronics’ CSR practices in India and their significant contributions to community welfare and sustainable development. It highlights the potential of corporate social responsibility as a powerful tool for driving positive social change and underscores the need for ongoing commitment and innovation in CSR strategies to meet the evolving needs of local communities.